2022
DOI: 10.1038/s41396-021-01175-7
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and biogeochemical analyses reveal insights into methanogenesis in deep subseafloor sediment at a biogenic gas hydrate site

Abstract: Gas hydrates deposited in subseafloor sediments are considered to primarily consist of biogenic methane. However, little evidence for the occurrence of living methanogens in subseafloor sediments has been provided. This study investigated viable methanogen diversity, population, physiology and potential activity in hydrate-bearing sediments (1–307 m below the seafloor) from the eastern Nankai Trough. Radiotracer experiments, the quantification of coenzyme F430 and molecular sequencing analysis indicated the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…These findings highlight the necessity of using a variety of marker genes to characterise a broader spectrum of the methanogenic diversity residing in this ecosystem. Similar results have been reported for anaerobic digesters [ 66 ], but studies in extreme environments are scarce [ 67 ].…”
Section: Discussionsupporting
confidence: 84%
“…These findings highlight the necessity of using a variety of marker genes to characterise a broader spectrum of the methanogenic diversity residing in this ecosystem. Similar results have been reported for anaerobic digesters [ 66 ], but studies in extreme environments are scarce [ 67 ].…”
Section: Discussionsupporting
confidence: 84%
“…Although the condition in the subseafloor was considered to be suitable for hydrogenotrophic or acetoclastic methanogenesis, we only detected H 2 -dependent methylotrophic methanogens (Methanomassiliicoccales and Methanofastidiosales), which produce methane using hydrogen, C1 substrates and synthesize biomass using acetate [63]. Similarly, in other reports about the sediments of JiaoLong, Shenhu and Haima methane seep from the South China Sea as well as hydrate-bearing sediments from eastern Nankai Trough, the H 2 -dependent methylotrophic methanogenesis was found to be a major methanogenic pathway [64][65][66][67]. The methylotrophic methanogenesis were reported to be able to unitize non-competitive substrates (methanol, methylamines, or methyl sulfide and so on) originated from the degradation of organic macromolecules such as lignin and pectin [68].…”
Section: Metagenomic Profiling Revealed That Microbial Community Comp...supporting
confidence: 67%
“…Previous studies showed that the abundance of methanogenesis genes increased with the mudflat sediment depth [ 66 ], and the composition of methanogens showed obvious variations in different ecosystems [ 6 , 67 ]. For example, hydrogenotrophic methanogenesis was dominated in a subseafloor sediment [ 68 ], peatlands [ 69 ] and mangrove sediments [ 70 ]. In this study, we observed a relatively high abundance of mcrA gene and an increasing trend along the sediment depth, suggesting a possibly more active methanogenesis in the deep sediment.…”
Section: Discussionmentioning
confidence: 99%